Mobile Journalism Practice in the Kompas.com Newsroom - Albertus Magnus Prestianta (Universitas Muhammadiyah Yogyakarta, 2022)
Smartphones and social media have changed how the media gather, produce, edit, and disseminate news. By employing the journalistic capital concept, this paper examines how journalists in Kompas.com, one of the pioneers of online media in Indonesia, incorporate mobile journalism practice into their work. This article explores how journalists and newsrooms respond to change that coincides with mobile devices and social media in the newsroom. The qualitative data analysis obtained from in-depth interviews with Kompas.com journalists and document analysis revealed that the application of mojo in Kompas.com is relatively new and is still looking for a form. Kompas.com integrate mobile smartphones into journalistic work to produce stories with a multimedia approach to meet changing journalistic and business needs. Journalists are expected to produce journalistic content in short videos using mobile devices related to daily events around them. Thus, the practice of mojo emerged as a new order in journalism. Kompas.com develops a multimedia division and improves journalists’ skills through training on all desks in the newsroom. Journalists learn new applications and tools and produce short videos for social media.